Factors That Influence Consumer Decisions In Buying Used Mobile Phones In Dairi District - Fajran Rahman Berutu; Sugianto Sugianto; Muhammad Irwan Padli Nasution (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2024)
Used cellphones are cellular telecommunications devices that have been previously used by other people and resold. Not a few people prefer to buy used cellphones rather than new cellphones. This research aims to analyze the factors that influence consumers' decisions in buying used cellphones in Dairi Regency. The subjects in this research were people from Dairi Regency who had bought used cellphones. The research method used is quantitative by obtaining data through questionnaires distributed to respondents. The data analysis technique used is multiple linear regression analysis. The research results showed that partially the price and quality of the product did not influence consumers' decisions to buy used cellphones in Dairi Regency. Partially, brand and physical condition have a positive influence on consumers' decisions to buy used cellphones in Dairi Regency. Meanwhile, simultaneously price and product quality have a positive influence on consumers' decisions to buy used cellphones in Dairi Regency.